Embajadores de Estados Unidos en Mexico: diplomacia de crisis y oportunidades. (El Colegio de Mexico, 2021)
The relationship with the United States, inescapable, intense and asymmetrical, has been a determining element in the history of Mexico. This book analyzes it from a particular vantage point: that of the experience of the representatives of the neighboring republic in this country. Fifteen authors --diplomats, historians, internationalists-- explore the management of seventeen United States plenipotentiaries who articulated their country's policy towards Mexico in moments of crisis, with diverse results. These diplomats contributed to defusing dangers and untying knots, preventing an essential relationship from sinking or making the atmosphere more difficult and narrowing the governments' margins of manoeuvre. These essays shed light, from a novel perspective, on the complexities of the binational relationship through the agenda, perceptions, and actions of the US envoys. These texts enrich our understanding of the past and we hope that they will help us draw a stronger, more fertile, more transparent and more equitable relationship for the future.